Effect of deflocculants on the rheological behavior of high alumina matrix suspensions for self-flowing bauxite castable - M. A., Trubinsin; L. V, Furda; V. V, Lisnyak; N. A., Volovicheva; Van Dat, Doan; Van Thuan, Le (Vietnam Journal of Science and Technology, 2024)
This study investigates the influence of commercially available polyphosphates and polycarboxylate ethers as deflocculants on aqueous suspensions containing high alumina cement (HAC), reactive alumina (RA), and various matrix compositions. Utilizing rheological methods, the research explores the interplay between dispersant concentration and the apparent viscosity and flow behavior of RA suspensions and matrix mixtures. The Casson model is employed to effectively describe the obtained flow data. Moreover, the study discerns specific impacts of polycarboxylate ethers on the thickening properties of matrix mixtures characterized by varying RA and HAC contents. Additionally, the research evaluates the physical and mechanical properties of low-cement bauxite castables treated with a range of polycarboxylate esters. The findings demonstrate that all deflocculated suspensions exhibit Non-Newtonian structured fluid behavior with a discernible yield stress (τ0) at shear rates below 20 s-1. At higher shear rates, there is a significant reduction in apparent viscosity, aligning well with the Casson model. Comparative assessments, based on flow curve values τ0, elucidate differing degrees of suspension flocculation depending on the type of dispersant used.